Corporate Social Responsibility in a Competitive Business Environment - Newman, Carol (My University, 2020)
Using a representative sample of more than 5,000 Vietnamese enterprises, we explore the firm-level productivity effects of corporate social responsibility (CSR). The data enables us to create 12 quantitative CSR measures, which can be grouped into two broader categories related to management and community-based CSR initiatives. We find a positive relationship between adoption of CSR initiatives and firm efficiency, and reveal that the impact is stronger for firms in non-competitive industries. Moreover, we show that local community focused CSR initiatives drive the aggregate effect. This suggests that socially responsible actions by firms are likely to pay-off when stakeholder engagement has a localised focus. We provide evidence of reciprocity by showing that employees accept a lower share of additionally generated value-added (controlling for productivity differences) in exchange for working in a company that signals ‘good’ corporate values.
PUBLISHED
Keywords: Corporate social responsibility; Vietnam; Efficiency; Corporate values; International Development; International Integration; Development Economics